(untitled) (KULT_online, 2009)
Literaturverfilmung: Perspektiven und Analysen (Literary Adaptation: Perspectives and Analyses) is an anthology edited by Eugenio Spedicato and Sven Hanuschekthat that brings together nine case studies. Although it lacks a conceptual introduction and framework, the volume compensates with an innovative selection of films and a broad spectrum of methodological approaches (from narratology, space theory, social history, and so forth). It is by all means worth reading for its highly accessible overview of the strengths and weaknesses of current research on film and literature.